Generic epitaxial graphene biosensors for ultrasensitive detection of cancer risk biomarker - Zari Tehrani (2D Materials, 2014)
A generic electrochemical method of 'bioreceptor' antibody attachment to phenyl amine functionalized graphitic surfaces is demonstrated. Micro-channels of chemically modified multi-layer epitaxial graphene (MLEG) have been used to provide a repeatable and reliable response to nano-molar (nM) concentrations of the cancer risk (oxidative stress) biomarker 8-hydroxydeoxyguanosine (8-OHdG). X-ray photoelectron spectroscopy, Raman spectroscopy are used to characterize the functionalized MLEG. Confocal fluorescence microscopy using fluorescent-labelled antibodies indicates that the anti-8-OHdG antibody selectively binds to the phenyl amine-functionalized MLEG's channel. Current–voltage measurements on functionalized channels showed repeatable current responses from antibody–biomarker binding events. This technique is scalable, reliable, and capable of providing a rapid, quantitative, label-free assessment of biomarkers at nano-molar (<20 nM) concentrations in analyte solutions. The sensitivity of the sensor device was investigated using varying concentrations of 8-OHdG, with changes in the sensor's channel resistance observed upon exposure to 8-OHdG. Detection of 8-OHdG concentrations as low as 0.1 ng ml−1 (0.35 nM) has been demonstrated. This is five times more sensitive than reported enzyme linked immunosorbent assay tests (0.5 ng ml−1).